Novel cinnamohydroxamic acid derivatives as HDAC inhibitors with anticancer activity in vitro and in vivo. (5th April 2016) - Wang, Lihui; Bao, Xuefei; Yang, Jingyu; Li, Huahuan; Zhou, Qifan; Jiang, Xiaorui; Li, Meng; Liu, Xing; Yuan, Xiangzhong; Sun, Yuhong; Chen, Junli; Zhang, Jingyuan; et al.
Abstract: A novel series of cinnamohydroxamic acid derivatives were synthesized and their biological activities against HDAC were assessed. Our results showed that the compound with more strong inhibitory activity to HDAC would exhibited more significant anti-proliferative effect on tumor cells. Among these compounds, 7e displayed clearly inhibitory effects on HDAC and tumor cell growth. Furthermore, HDAC isoforms enzyme data indicated that, compared to HDAC pan-inhibitor SAHA, 7e owned an enhanced inhibitory effect on HDAC1, 3 and 6 isoforms. Meanwhile, it also significantly suppressed cell growth of lung cancer cells compared to SAHA, but with lower toxicity in normal cells. Mechanistically, 7e prompted acetylation of histone3 and histone4, led to up-regulation of p21, and then mediated cell cycle arrest and pro-apoptosis. Moreover, the in vivo study indicated that compound 7e could retard tumor growth of A549 xenograft models. These findings support the further investigation on the anti-tumor potential of this class of compounds as HDAC inhibitor. Graphical abstract: Highlights: 7e, a cinnamohydroxamic acid derivative, suppresses HDAC activity. 7e prompts cell cycle arrest and induces cell apoptosis. 7e inhibits tumor growth but with lower toxicity in vitro and in vivo .